FAKTOR DETERMINAN PERILAKU CUCI TANGAN PAKAI SABUN (CTPS) PADA MASYARAKAT DI TANAH KALIKEDINDING - Gracia Risnawaty (Universitas Airlangga, 2016)
One of the factors that are considered important for the development of social welfare inIndonesia is health. Based on data from the WHO, diarrhea and ARI (Acute Respiratory Infection) is aninfectious disease remains a health problem in Indonesia. From the data obtained in 2015, it is knownthat the village Tanah Kalikedinding RW II (RT 07 and 11) has a health problem with the number ofdiarrhea and ARI are quite high, as many as 2.467 cases of diarrhea and 15.207 cases for patients withrespiratory infection. The purpose of this research is to fi nd information about the relationship betweenknowledge and attitudes toward behavior handwashing (CTPS) in the village Tanah Kalikedinding. Theresearch method is analytic with cross sectional approach. The population in this study is the wholecommunity in the village Tanah Kalikedinding. A total sample of 70 people were selected using simplerandom sampling. The research variables are gender, age, knowledge, education, employm ent, attitudesand behaviors CTPS. The primary data obtained from interviews and questionnaires, while secondarydata obtained from the data clinic. The results showed a determinant factor in the behavior of people inthe CTPS divided into three driving factors are gender, age, knowledge, education, employment, attitudesand behaviors CTPS, enabling factors such as facility and reinforcing factors are health workers. Itis necessary to attempt a programmed extension activities, sustainable, evaluation and monitoring atregular intervals in each program activity CTPS on society as well as involving cross-sector cooperationin every program CTPS on society.Keywords: knowledge, attitudes, behavior, CTPS